Developing treatment guidelines for myasthenia gravis. Issue 1 (30th January 2018) - Sanders, Donald B.; Wolfe, Gil I.; Narayanaswami, Pushpa; ,
Abstract: A task force of the Myasthenia Gravis Foundation of America recently published a formal consensus statement intended to be a treatment guide for clinicians caring for myasthenia gravis (MG) patients worldwide. Its development was stimulated by the fact that there is generally no accepted standard of care for MG, and no one treatment is best for all MG patients. Also, there are few randomized trials of treatments in current use, and the generalizability of the few trials that have been successful may be difficult. Fifteen international experts in MG participated in the consensus process, which used a simple consensus to develop preliminary definitions and the RAND/UCLA Appropriateness Method to quantify agreement on treatment guidance statements for seven topics: symptomatic and immunosuppressive treatment, intravenous immunoglobulin and plasma exchange, impending and manifest myasthenic crisis, thymectomy, juvenile MG, MG with muscle‐specific tyrosine kinase antibodies, and MG in pregnancy. The executive summary of the guidance statement was published with open access to facilitate access by patients and healthcare professionals, and the full statement, with extensive background information, is available online. The guidance statement is a living document that will require updates as new treatments and new information on current treatments become available.